Pulmonary Changes in Preterm Neonates with Hyaline Membrane Disease (a Clinicomorphological Study) - A. M. Golubev; S. A. Perepelitsa; Ye. F. Smerdova; V. V., Moroz; Yu. M. Avakyan; S. V Kachigurova; V. N. Yakovtsev (Общая реаниматология)
Objective: to reveal lung morphological changes in preterm neonatal infants with hyaline membrane disease (HMD) in the use of exogenous surfactants and artificial ventilation. Materials and methods. Case histories and autopsy protocols were analyzed in 90 preterm neonates who had died from severe respiratory failure. All the neonates were divided into 4 groups: 1) 20 (22.2%) infants who had received the exogenous surfactant Curosurf in the combined therapy of HMD; 2) 19 (21.1%) babies with HMD who had taken Surfactant BL; 3) 25 (27.8%) surfactant-untreated infants who had died from HMD; 4) 26 (28.9%) very preterm neonates with extremely low birth weight who had died within the first hour of life. The lungs were histologically and morphometrically examined. Results. The study demonstrated the specific course of HMD when exogenous surfactants and artificial ventilation were used. The contributors to the development of the disease are intranatal amniotic fluid aspiration and intranatal fetal hypoxia. Conclusion. Artificial ventilation and the use of exogenous surfactants do not block the generation of hyaline membranes. The latter differ in formation time, form, and location. The differences in a cell response to hyaline membranes were found in the neonatal infants receiving exogenous surfactants. The characteristic morphological signs of the disease for all the neonates enrolled in the study are alveolar and bronchial epithelial damages and microcirculatory disorders. Key words: preterm neonatal infants, hyaline membrane disease, exogenous surfactants, artificial ventilation, histology, morphometry.